1992
DOI: 10.1002/gcc.2870050403
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of the transcription factor gene CHOP in myxoid liposarcomas with t(12;16)(q13;p11)

Abstract: Most myxoid liposarcomas (MLS) are characterized cytogenetically by a t(12;16)(q13;p11). It is reasonable to assume that this translocation corresponds to the consistent rearrangement of one or two genes in 12q13 and/or 16p11, and that the loci thus affected are important in the normal control of fat cell differentiation and proliferation. We have used Southern blot technique to test whether a gene of the CCAAT/enhancer binding protein (C/EBP) family, CHOP, which maps to 12q13 and is assumed to be involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
158
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 284 publications
(164 citation statements)
references
References 33 publications
4
158
0
2
Order By: Relevance
“…The MLS cell line MLS 402-91 (Å man et al, 1992;ThelinJa¨rnum et al, 1999) and human fibrosarcoma cell lines HT1080, HT1080 DDIT3-GFP and HT1080 FUS-DDIT3-GFP (Engstro¨m et al, 2006) were kept frozen in liquid nitrogen or cultured at 37 1C and 5% CO 2 in RPMI 1640 medium with HEPES (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid) buffer supplemented with 2 mM L-glutamine, 50 U/ml penicillin, 50 mg/ml streptomycin and 8% fetal calf serum (Invitrogen, Carlsbad, CA, USA). G418 (200 mg/ml, Invitrogen) was constantly added to cell lines HT1080 FUSA-GFP, HT1080 DDIT3-GFP and HT1080 FUS-DDIT3-GFP to ensure stable expression of GFP constructs in the cell population.…”
Section: Cell Linesmentioning
confidence: 99%
“…The MLS cell line MLS 402-91 (Å man et al, 1992;ThelinJa¨rnum et al, 1999) and human fibrosarcoma cell lines HT1080, HT1080 DDIT3-GFP and HT1080 FUS-DDIT3-GFP (Engstro¨m et al, 2006) were kept frozen in liquid nitrogen or cultured at 37 1C and 5% CO 2 in RPMI 1640 medium with HEPES (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid) buffer supplemented with 2 mM L-glutamine, 50 U/ml penicillin, 50 mg/ml streptomycin and 8% fetal calf serum (Invitrogen, Carlsbad, CA, USA). G418 (200 mg/ml, Invitrogen) was constantly added to cell lines HT1080 FUSA-GFP, HT1080 DDIT3-GFP and HT1080 FUS-DDIT3-GFP to ensure stable expression of GFP constructs in the cell population.…”
Section: Cell Linesmentioning
confidence: 99%
“…(27) have shown that HMGA2 protein suppression results in growth inhibition of HMGA2-overexpressing primary cell cultures of well-differentiated liposarcoma, indicating that HMGA2 plays an important role in the growth of these tumors. The cytogenetic hallmark of myxoid liposarcoma is the presence of t(12;16)(q13;p11) that leads to the formation of the FUS-DDIT3 fusion protein (28)(29)(30)(31). In contrast to well-differentiated liposarcoma, the HMGA2 gene is not amplified in myxoid liposarcoma.…”
Section: A Positive Correlation Between Hmga2 and Imp2 Gene Expressiomentioning
confidence: 99%
“…(also referred to as TLS for translocated in liposarcoma) (Aman et al 1992, Rabbits et al 1993. The CHOP gene possesses a leucine zipper dimerization domain, whereby the protein can bind to C/EBP-like proteins and block their interaction with DNA.…”
Section: Molecular and Cytogenetics Of Soft Tissue Sarcomasmentioning
confidence: 99%